Occurrence of premature regression of corpus luteum in MOET programs in Dorper ewes under subtropical climate - Rocha, Marcela S.; Maia, Ana Lucia R.S.; Rangel, Paulo Sérgio C.; Oliveira, Maria Emilia F. [UNESP]; Fonseca, Jeferson F.; Oliveira, Cláudio A.; Souza-Fabjan, Joanna M.G. (My University, 2022)
Premature regression of corpus luteum (PRCL) is a functional alteration that occurs mainly in superovulated females hampering the widespread use of multiple ovulation and embryo transfer (MOET). This study evaluated the association of donor age (3–9 years old), body condition score (2 to 4.5), number of MOET (1 to 5) repetitions and season (breeding, transition, or non-breeding) with the occurrence of PRCL in ewes. Multiparous Dorper ewes (n = 44) were subjected to MOET during four consecutive years, with the same superovulatory treatment. Before embryo collection, ovaries were laparoscopically performed to assess the corpora lutea (CL). Overall, the total PRCL occurrence was 24.7% (26/105) and it had no association with the studied factors. Percentages of ewes that presented PRCL once or twice were 45.5% (20/44) and 6.8% (3/44), respectively, while the percentage of ewes that had no PRCL was 47.7% (21/44). Proportions of PRCL were similar (P > 0.05) among breeding (21%), transition (31%), and non-breeding (24%) season; and also (P > 0.05) in lower/thin (20%), average/good (24%), and higher/fat (29%) females. In conclusion, although this phenomenon had no association to the factors studied, the occurrence of PRCL affects ∼25% of ewes subjected to MOET procedures and future alternatives to circumvent this obstacle need to be developed.
Keywords: Abnormal CL; Luteal dysfunction; Seasonality, Sheep; Superovulation